2007
DOI: 10.1097/iio.0b013e3180377936
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation and Infection in Age-related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) affects more than 1.75 million individuals in the United States and is the leading cause of blindness in persons over the age of 65 in Western countries. 1 The earliest signs of AMD include drusen and changes in the retinal pigment epithelium (RPE). Late changes include geographic atrophy and choroidal neovascularization (CNV). AMD is broadly classified into dry and neovascular forms. Dry AMD is characterized by the presence of drusen (localized deposits between the RPE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…These persistent changes, coupled with an IFN␥-driven increase in choroidal cell proliferation, suggest a pathway for the entry of choroidal neovascular blood vessels into the SRS via the RPE tight junctions. These mechanisms provide a basis for understanding the role of inflammation in choroidal neovascularization and AMD (4,50,65).…”
Section: Discussionmentioning
confidence: 99%
“…These persistent changes, coupled with an IFN␥-driven increase in choroidal cell proliferation, suggest a pathway for the entry of choroidal neovascular blood vessels into the SRS via the RPE tight junctions. These mechanisms provide a basis for understanding the role of inflammation in choroidal neovascularization and AMD (4,50,65).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 During the late stage of the disease, more evidence can be found for inflammatory involvement. 25,28 The immunological protein expression profile in Ccl2…”
Section: Cx3cr1mentioning
confidence: 99%
“…Immunohistochemical and molecular genetic evidence of chronic inflammation in affected tissue is seen in Alzheimer's disease (AD) [1], Parkinson's disease (PD) [2], multiple sclerosis (MS) [3] and in age-related macular degeneration (AMD) [4]. More than 20 epidemiological studies indicated that the chronic use of nonsteroidal anti-inflammatory drugs (NSAIDs) greatly reduced the risk of AD, testifying the importance of inflammatory reaction in AD.…”
Section: Introductionmentioning
confidence: 99%